Stool Banking for Fecal Microbiota Transplantation: Methods and Operations at a Large Stool Bank - Chen, Justin; Zaman, Amanda; Ramakrishna, Bharat; Olesen, Scott W. (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives: Fecal microbiota transplantation (FMT) is a recommended therapy for recurrent Clostridioides difficile infection and is being investigated as a potential therapy for dozens of microbiome-mediated indications. Stool banks centralize FMT donor screening and FMT material preparation with the goal of improving the safety, quality, convenience, and accessibility of FMT material. Although there are published consensuses on donor screening guidelines, there are few reports about the implementation of those guidelines in functioning stool banks. Methods: To help inform consensus standards with data gathered from real-world settings and, in turn, to improve patient care, here we describe the general methodology used in 2018 by OpenBiome, a large stool bank, and its outputs in that year. Results: In 2018, the stool bank received 7,536 stool donations from 210 donors, a daily average of 20.6 donations, and processed 4,271 of those donations into FMT preparations. The median time a screened and enrolled stool donor actively donated stool was 5.8 months. The median time between the manufacture of an FMT preparation and its shipment to a hospital or physician was 8.9 months. Half of the stool bank’s partner hospitals and physicians ordered an average of 0.75 or fewer FMT preparations per month. Conclusions: Further knowledge sharing should help inform refinements of stool banking guidelines and best practices.